1999
DOI: 10.1021/js980258b
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible fentanyl doses delivered intermittently at different time intervals from an electrotransport system

Abstract: The electrotransport transdermal fentanyl system (ET [fentanyl]), uses a small electrical current to enhance delivery of fentanyl to systemic circulation. Intermittent doses can be administered by periodic application of the current. The purpose of this study was to compare the effects of the frequency of intermittent drug delivery by ET (fentanyl) and compare the drug delivery to systemic circulation by ET (fentanyl) with intravenous administration. The topical safety was also determined for the ET (fentanyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…This operates in a similar manner to the Vyteris system. The NDA application is based on the ability of this system to enhance the delivery of fentanyl into the systemic circulation via the skin (Gupta et al 1998(Gupta et al , 1999. Fentanyl is an opioid analgesic used in the treatment of acute pain and the E-TRANS fentanyl system reportedly allows patient-controlled delivery of this pain medication and represents an improvement in pain management compared with intravenous injections and oral dosing methods (Alza 2005).…”
Section: Iontophoresismentioning
confidence: 99%
“…This operates in a similar manner to the Vyteris system. The NDA application is based on the ability of this system to enhance the delivery of fentanyl into the systemic circulation via the skin (Gupta et al 1998(Gupta et al , 1999. Fentanyl is an opioid analgesic used in the treatment of acute pain and the E-TRANS fentanyl system reportedly allows patient-controlled delivery of this pain medication and represents an improvement in pain management compared with intravenous injections and oral dosing methods (Alza 2005).…”
Section: Iontophoresismentioning
confidence: 99%
“…[67][68][69][70] Fentanyl, a shortacting synthetic opioid, has been used safely and effectively for 30 years to manage both acute and chronic pain. [71][72][73] Unlike morphine, fentanyl does not have active metabolites that accumulate over time. 74 Pharmacokinetic stud-CHRISTINE MIASKOWSKI 258 ies have shown that absorption of fentanyl from the PCTS system is not affected by demographic characteristics such as age, gender, ethnicity, or body weight.…”
mentioning
confidence: 99%
“…Improved drug permeation as a result of this methodology can be attributed to either one or a combination of the following mechanisms: Electro-repulsion (for charged solutes), electro-osmosis (for uncharged solutes) and electro-pertubation (for both charged and uncharged). Various iontophoretic devices are currently under commercial development including the Phoresor device developed by Iomed Inc. and the Vyteris and E-TRANS devices developed by Alza Corp 6,7 .…”
Section: Physical Techniquesmentioning
confidence: 99%